+0  
 
0
3
1
avatar+523 

Let a and b be the solutions to 7x^2 + x - 5 = 6x^2 - 4x + 5. Compute (a - 4b)(b - 4a).

 Apr 1, 2024
 #1
avatar+128399 
+1

Simplify as

 

x^2 + 5x - 10   =   0 

Product of  solutions =   ab  =  -10

Sum of  solutions =  a + b =  -5         square both sides

a^2 + 2ab + b^2  =  25

a^2 + 2(-10) + b^2  =  25

a^2 + b^2  = 45

 

(a - 4b) (b - 4a)  = 

 

ab - 4b^2 - 4a^2 + 16ab  = 

 

17ab  - 4 ( a^2 + b^2)  =

 

17 (-10)  - 4 ( 45)  =

 

-170 - 180  =

 

- 350

 

cool cool cool

 Apr 1, 2024

0 Online Users